The Significance of Spiritual Leadership in Redefining the Culture of Sustainable Quality: The Process of Internalizing Values - Muhyidin Muhyidin; Abu Yasid Albustomi (Universitas Nurul Jadid Probolinggo, Indonesia, 2025)
This study examines the role of spiritual leadership in forming a sustainable quality culture in Islamic Religious Higher Education Institutions (PTKI), with a case study at Nurul Jadid University. Amid global quality demands, PTKI faces a unique challenge in integrating Islamic values with modern management systems. The research problem focuses on the empirical exploration of how PTKI leaders, through their dual roles as managers and spiritual role models, succeed in internalizing religious values as the foundation of quality. Using an interpretive phenomenological approach, this study explores the subjective experiences of leaders and staff through in-depth interviews, observations, and document analysis. Key findings suggest that spiritual leadership has a significant influence on the formation of a work ethic based on sincerity and responsibility, transforming the perception of work into a form of worship and encouraging intrinsic commitment. Religious values, such as trust and honesty, are explicitly translated into institutional quality management policies and procedures, bridging potential ambiguities between religious and managerial authorities. Furthermore, spiritual leadership has proven to be a transformative force in instilling an ethos of excellent service, which is manifested in the proactive actions and empathy of the academic community. The implications include recommendations to integrate the spiritual dimension in higher education accreditation policies and leadership practices at PTKI, in order to achieve holistic and sustainable excellence.